Cost-effectiveness analysis of transnasal fentanyl citrate for the treatment of breakthrough cancer pain. (June 2014) - Ruggeri, Matteo; Turriziani, Adriana; Oradei, Marco
<x xml:space="preserve">Abstract</x> Introduction: Pain is a symptom of cancer and is categorized in two forms: background pain to be treated with analgesics, and breakthrough cancer pain (BTcP), which needs drug treatment on demand. We present a cost-effectiveness analysis of transnasal fentanyl citrate as an alternative to morphine. Methods: A Markov model considers a cohort of 100 patients on a daily basis. Effectiveness was included by selecting three clinical studies. Side effects, hospitalizations and visits were valued by referring to national formularies. Utility data were used to differentiate the health status inherent to BTcP. Results: The incremental cost-effectiveness ratio of transnasal fentanyl citrate is 10, 140 euros/QALY. Sensitivity analysis shows that with a threshold of 30, 000 euros/QALY, the treatment of BTcP with transnasal fentanyl citrate would have an 86% probability of being cost-effective. Conclusion: Transnasal Fentanyl citrate is cost-effective, therefore represents a good investment in health.